NEEDS ANALYSIS OF LEARNING ANIMATION MEDIA ON THE FIQH SUBJECT GRADE VI MI AL-MUSTAWA GUNUNG SINDUR BOGOR: Analisis Kebutuhan Media Animasi Pembelajaran Pada Mata Pelajaran Fiqih Kelas VI MI Al-Mustawa - Atqiya, Mufqi; Muhyidin Nurzaelani, Mohammad; Wiranata, Afif (EDUCATE : Jurnal Teknologi Pendidikan, 2024)
Learning Fiqh about menstruation is still considered abstract, and the proposed solution is to use learning animation media to make it more concrete. However, the development of this animation must be adapted to the needs of students, so a needs analysis is needed. This research aims to analyze the needs for creating learning animations required by students at MI Al-Mustawa. This research is qualitative and involves the participation of students and class VI teachers at MI Al-Mustawa. The data collection method used was interviews. The research results show that students need learning media that is able to visualize images in a realistic and non-monotonous way so that they can play an active role in learning.